2012
DOI: 10.1016/j.mambio.2012.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Differential patterns of home-range, net displacement and resting sites use of Conepatus chinga in southern Brazil

Abstract: a b s t r a c tStudies on the spatial ecology of Molina's hog-nosed skunk were conducted in southern Brazil. Between individuals were tagged with radio collars and monitored by radiotelemetry (VHF). The average home-range estimated for 12 skunks was 1.63 km 2 ± 1.17 km 2 . Males had home-ranges 2.5 times larger than females, and also showed significantly larger patterns of displacement. These differences in space probably were related not only to sexual size dimorphism, but also to differential behavior betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 24 publications
2
17
0
1
Order By: Relevance
“…Thus, the robust humerus of Cyonasua (relatively high HRI value) is related to the ability to resist relatively high bending and shearing stresses, which would be associated with supporting their body mass (body mass average for Cyonasua : 19.5 kg., greater than any extant procyonid; Tarquini et al, ), as could be suggested by the low but significant positive allometry of HRI. However, given that the HRI values of Cyonasua were close to those of Nasua , Nasuella, and Conepatus , genera in which body masses are small to moderate (4.5 kg on average for Nasua , Gompper, ; Gompper & Decker, ; 1.34 kg for Nasuella , Jones et al, ; 2 kg on average for Conepatus , Kasper et al, ), but all of which are specialized diggers among carnivorans, it is likely that this robustness is related to stresses caused by active use of the forearm in digging, rather than supporting body mass. In this sense, Cyonasua shows values of HRI that coincide with the median for the SU‐specialized‐digger category.…”
Section: Discussionmentioning
confidence: 91%
“…Thus, the robust humerus of Cyonasua (relatively high HRI value) is related to the ability to resist relatively high bending and shearing stresses, which would be associated with supporting their body mass (body mass average for Cyonasua : 19.5 kg., greater than any extant procyonid; Tarquini et al, ), as could be suggested by the low but significant positive allometry of HRI. However, given that the HRI values of Cyonasua were close to those of Nasua , Nasuella, and Conepatus , genera in which body masses are small to moderate (4.5 kg on average for Nasua , Gompper, ; Gompper & Decker, ; 1.34 kg for Nasuella , Jones et al, ; 2 kg on average for Conepatus , Kasper et al, ), but all of which are specialized diggers among carnivorans, it is likely that this robustness is related to stresses caused by active use of the forearm in digging, rather than supporting body mass. In this sense, Cyonasua shows values of HRI that coincide with the median for the SU‐specialized‐digger category.…”
Section: Discussionmentioning
confidence: 91%
“…We found no evidence of consumption of eggs, but they probably represent an important energy source in some regions, such as the coastal regions of southern Brazil and Uruguay, where Gonçalves et al (2007) reported the predation of 98% of turtle nests, 31% of them by Conepatus chinga. In a study of the spatial ecology of C. chinga, Kasper et al (2012b) recorded several instances of skunks preying on turtle and bird nests to eat eggs, mainly in summer.…”
Section: Discussionmentioning
confidence: 99%
“…There is little information available regarding the home ranges of other Mepbitid species in South American, aside from a few area estimates ranging from 1.95 to 0.55 km^ for C. chinga (Donadio et al, 2001;Reppucci et al, 2009;Kasper et al, 2012a) and 0.09 to 0.16 km^ for C. Humboldt (Fuller et al, 1987;Johnson et al, 1988), which are summarized in table 2. Different methods, different ecological requirements of each species, tbe relative abundance of Sunquist et al,, 1989 This study Kasperetal,, 2012bKasper et al, 2012bReppucci et al,, 2009Donadio et al,, 2001Fuller et al, 1987Fuller et al, 1987Fuller et al, 1987Johnson et al, 1988Johnson et al, 1988Johnson et al, 1988 Juvenile. resources and the degree of environmental disturbance where each population is located, may all have an influence on this variation.…”
Section: Home Rangementioning
confidence: 94%
“…In North America, other species of the skunk Family Mephitidae have received greater attention because some of them may be vectors for rabies (WadeSmith & Verts, 1982), and in some rare instances cause crop damage (Olson & Lewis, 1999), while other species have shown dramatic population declines (Gompper & Hackett, 2005). For species occurring in South America, data on activity patterns, home range and habitat use (Donadio et al, 2001;Kasper et al, 2009;Reppucci et al, 2009;Kasper et al, 2012b), diet (Travaini et al, 1998;Donadio et al, 2004;Montalvo et al, 2008), and abundance (Kasper et al, 2012a) have been collected for C. chinga. Also, Johnson et al (1988) discussed the influence of seasonal changes on the activity patterns of C. humboldti and assessed the home range area of this species in Chile.…”
Section: Introductionmentioning
confidence: 99%